Growth and Equity in Tertiary Education in Sub-Saharan Africa - Darvas, Peter; Ballal, Sonali; Feda, Kedebe (International Journal of African Higher Education, 2014)
This study represents a first report of a regional cross-country analysis of patterns in equity and growth in tertiary education in Sub-Saharan Africa. In it, we analyse country-level surveys and regional statistics to see how expansion affected equity, how equity is explained by household characteristics and other factors, and what the intrinsic characteristics of the tertiary education system are that influence equity. Data show that in many instances, Sub-Saharan African countries fall behind other regions in terms of equity; and whereas some policies, such as diversification and more equitable pre-tertiary education can help, more efforts and more effective policies need to be introduced to make the system more equitable. The report argues that growth itself will not necessarily lead to improved equity and more equitable access to tertiary education can help the sector in achieving its higher-level objectives, including its contribution to competitiveness and prosperity. Cette étude constitue le premier rapport d’une analyse de l’équité et de la croissance de l’enseignement supérieur en Afrique sub-saharienne. Nous analysons des enquêtes nationales et des statistiques régionales pour montrer la manière dont la croissance affecte l’équité, comment l’équité peut être expliquée par les caractéristiques des ménages ainsi que par d’autres facteurs et quels facteurs propres au système d’enseignement supérieur influencent l’équité. Les données montrent que, dans de nombreux cas, les pays d’Afrique sub-saharienne sont en retard par rapport à ceux d’autres régions en ce qui concerne l’équité. Tandis que certaines mesures politiques, comme diversifier l’enseignement supérieur ou rendre les enseignements primaire et secondaire plus équitables, peuvent aider, des efforts plus importants et des mesures politiques plus efficaces doivent être mis en place pour rendre le système plus équitable. Ce rapport soutient que la croissance ne conduira pas forcément à l’amélioration de l’équité et qu’un accès plus équitable à l’enseignement supérieur peut aider le secteur à atteindre ses objectifs les plus ambitieux, notamment contribuer à la compétitivité et la prospérité du pays et de la région.